Recognition of a person missing in the context of the events of 2014 in Ukraine - Trufanova, Yuliia; Manuliak, Nadiia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2021)
This article presents a legal analysis of the concept of recognizing a person as missing. The approaches of various scientists, in particular, Ukrainian and foreign, to the concept of a person who is unknown are revealed. The problematic issues arising in the course of the practical application of the institution of recognizing a person as missing and declaring him dead are considered, in particular, the problem of recognizing a person as missing, an individual who has gone missing in connection with military actions, an armed conflict. The article analyzes the legislation of Ukraine on recognizing a person as missing in the aspect of the present and in the context of 2014 in Ukraine. The problematic issues that arise during the practical application of the institution of declaring a person missing and declaring him dead are considered, in particular, the problems of declaring a person missing, a natural person who went missing due to hostilities and armed conflict. The institution of declaring a citizen missing and declaring him dead in general aims to protect the rights of citizens in connection with the termination of the civil relations in which they are participants. If we take into account the legal practice itself, it can be seen that there are always situations when to eliminate uncertainty in civil relations have to resort to the institution of declaring a citizen missing or declared dead. An analysis of current legislation and proposals to address the existing conflicts and gaps identified in this article may provide an impetus to improve existing legislation to protect the personal rights of persons who have been declared missing or deceased and have appeared. A separate category of individuals who can be declared missing in modern conditions are representatives of law enforcement and other law enforcement agencies, which are divided into three groups: a) could be killed or executed in captivity, whose bodies could remain on the battlefield or buried in the nameless graves; b) who are allegedly forcibly held captive by illegal armed groups; c) there is a probability of their transition to the side of the enemy or escape from the area of environmental protection or the territory of another armed conflict. This division will help to improve the conditions for declaring a person missing or declaring him dead in the context of setting the terms of such recognition.